Mycorrhizae, invasions, and the temporal dynamics of mutualism disruption. (20th October 2017) - Grove, Sara; Haubensak, Karen A.; Gehring, Catherine; Parker, Ingrid M.
Summary: An increasingly recognized impact of plant invaders is the disruption of positive interactions between native plants and their belowground mutualistic mycorrhizal fungi. We reviewed 112 studies from 61 publications that report invader impacts on mycorrhizal fungi. We describe emerging patterns on the frequency of negative, neutral and positive invader effects on mycorrhizal fungal abundance, richness and community composition, and we evaluate how these outcomes vary with invasion age. We also describe the evidence for three mechanisms of disruption: (1) plant‐plant competition that alters host quantity or quality (2) changes in soil properties such as nutrient availability and (3) allelopathy. Invaders can disrupt native mutualisms if they are non‐mycorrhizal, associate with a different type of mycorrhiza, or associate with different taxa of the same type of mycorrhiza as the native plants. Invaders that enrich soil nutrients can cause declines in mycorrhizal abundance, shifts in fungal community composition, and cause native plants to reduce their dependence on mycorrhizas. Invaders that produce allelopathic compounds cause mycorrhizal abundance to decrease and alter community composition because of variation in the sensitivity of different fungi to toxins. While the evidence for disruption of the mycorrhizal mutualism with invasion is strong, temporal patterns have not yet emerged from the literature. Invasion age was not clearly associated with extent of disruption, and the timing of recovery following invader removal was highly variable. Differences in the biology of native and invasive plants, their interactions with mycorrhizal fungi and the surrounding landscape contributed to this variation. Synthesis . Our systematic review suggests that invaders frequently decrease mycorrhizal abundance and alter fungal community composition while only occasionally affecting fungal species richness. The development of invader impacts, as well as the restoration of native communities after invader removal, are influenced by a suite of plant, fungal and environmental traits that change over time. However, few studies have examined the temporal dynamics of mycorrhizal disruption, and results are variable. Future research should focus on the temporal scale of mutualism disruption while considering plant phylogenetics and demography, fungal functional traits such as spore longevity and dispersal, and soil chemistry. Abstract : Our systematic review suggests that invaders frequently decrease mycorrhizal abundance and alter fungal community composition while only occasionally affecting fungal species richness. The development of invader impacts, as well as the restoration of native communities after invader removal, are influenced by a suite of plant, fungal and environmental traits that change over time. However, few studies have examined the temporal dynamics of mycorrhizal disruption, and results are variable. Future research should focus on the temporal scale of mutualism disruption while considering plant phylogenetics and demography, fungal functional traits such as spore longevity and dispersal, and soil chemistry.